The Father of Heart Transplantation Vladimir P. Demikhov - Oppedisano, Mikhail GL; Artyukh, Linard Yu; Karelina, Natalya R (Medicina Historica, 2021)
The article discusses the life’s work of the great Soviet scientist in the fields of transplantology, physiology and experimental surgery Vladimir Demikhov. He was the first to ever perform a heart and a cardiopulmonary system transplantation, as well as transplantation of other vital organs. He was also the first to perform head transplantation on a dog. Demikhov should have become a legend of Soviet medicine but did not find support from the government and ministers of health in particular, and was undeservingly forgotten. The following article is an attempt to give tribute to the memory of this great man, whose mind and thinking were ahead of their time by decades or maybe century.